Early (Bi-)Literacy – mit mehr als einer Sprache unterwegs zur Schrift(lichkeit): Potenziale mehrsprachiger Bilderbücher im Kontext durchgängiger Sprachbildung - Nauwerck, Patricia (Gyermeknevelés Tudományos Folyóirat, 2023)
For a long time, in the context of early second language acquistion/early foreign language learning, the focus was on spoken everyday language. As a result, many children were able to communicate successfully in everyday life, but failed in school tasks due to insufficiently developed language domains and a low level of verbal academic performance („hidden language difficulties“). In order to make the transition to school learning easier early literacy approaches have recently been established in the pre-school education. In this paper I will focus on early biliteracy discussing the potential of multilingual picture books to initiate cognitive academic language skills. Furthermore methodological suggestions are shown.